Physical drivers of chlorophyll and nutrients variability in the Southern-Central Arabian Gulf. (5th April 2023) - Al-Thani, Jassem A.; Soliman, Yousria; Al-Maslamani, Ibrahim A.; Yigiterhan, Oguz; Al-Ansari, Ebrahim M.A.S.
Abstract: The southern-central Arabian Gulf demonstrates a poor understanding of nutrients and chlorophyll dynamics in physical-biogeochemical settings. Here, using data of chlorophyll, nutrients and hydrographic parameters collected in two cruises in summer 2019 and winter 2020, we examined variability in nutrients and chlorophyll concentrations, and the driving mechanisms. Summer thermal stratification enhanced by intrusion of fresher surface water plume from the Arabian Sea developed a hypoxic zone (DO < 2.0 mL/L) below the thermocline. Nitrate and ammonium summer concentrations (2.24 ± 0.36, 1.70 ± 0.17 μM) were about 3 times the winter concentrations. Nutrient stoichiometry showed a Redfield-like nitrogen/phosphorus (N:P) ratio in summer (15.9:1) and a nitrogen limitation in winter (N:P = 4:1). Chlorophyll-a content in summer (mean = 0.80 mg/m 3 ) was about 1.4 times the winter concentration (mean = 0.58 mg/m 3 ) (p > 0.05). Photo-protective carotenoids content in summer (0.59 mg/m 3 ) was about 2.7 times their winter concentration. Winter cooling resulted in downwelling of dense water on the shallow coastal banks, which enhanced near bottom oxygen concentrations and swept away nutrient-rich water resulting in lower winter chlorophyll. This research features aspects of the physical and biogeochemical drivers underpinning the dynamics of nutrients and chlorophyll in the central Gulf. Graphical abstract: Image 1 Highlights: Concentrations of nutrients and chlorophyll are measured in two seasons. Extreme summer temperatures of the Arabian Gulf developed thermal stratification. Summer stratification is enhanced by the intrusion of the IOSW developing hypoxia. Downwelling of dense cold water in winter decreased nutrients at coastal waters. Chlorophyll and nutrients concentrations were higher in summer compared to winter.